A Computational Investigation of π-π Interactions in a Variety of Benzene Derivatives: A Computational Investigation of π-π Interactions in a Variety of Benzene Derivatives - Akhter, Shamima; Islam, Md Safiqul; Islam, Md Saiful (Dhaka University Journal of Science, 2025)
A theoretical calculation into π-π interactions of several benzene derivatives, including aniline, benzonitrile, chlorobenzene, phenol, and toluene, was conducted and documented. All structures have been optimized using the MP2/aug-cc-pVDZ theoretical method. Homodimer of benzene derivatives with various geometrical configurations, including face-to-face, anti-face-to-face, slipped-parallel, and T-shape, have been explored. Variations have been made to the distance between two molecules of each dimer while conserving the geometry of each structure, as determined via geometry optimization. The potential energy curve has been drawn for each configuration, and all of the data for each configuration has been fitted to a polynomial equation. For each configuration, the minimal distance between two molecules at which the interaction energy is the lowest has been determined using a polynomial equation. At distances of 3.47 Å, the slipped parallel structure of aniline is the most stable, with interaction energies of -8.92 kcalmol-1. At 3.41 Å, the anti-face-to-face structure of benzonitrile has the lowest interaction energy of -11.51 kcalmol-1, making it the most stable configuration. At 3.65 Å, the most stable form of chlorobenzene is slipped parallel, which has an interaction energy of -11.14 kcalmol-1. At distances of 3.81 Å and 3.69 Å, phenol and toluene exhibit interaction energies of -10.77 kcalmol- 1 and -10.43 kcalmol-1, respectively. The goal of π-π interactions is to provide a more comprehensive and more up-to-date understanding of the way this interaction works in fields like molecular biology. Dhaka Univ. J. Sci. 73(2): 151-160-68, 2025 (July)